TRANSGRESSION AND SECRET IN A POEM BY FLORBELA ESPANCA - Junior, José Leite Oliveira (2013)
This article is a semiotic analysis of the poem "Amar!", by the Portuguese writer Florbela Espanca. This text approaches the problem of the apparent contradiction between the traditional sonnet form and the transgressive content. Following the generative process, with emphasis on the discursive level, it is concluded that the use of the sonnet can be undestood as the veridictory modality of secret to the cognitive subject, because the appearing is negative and the transgressive being, thematized by free love, is asserted.